(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article represents aphorism as a short, precise expression that transmits a generalized, complete thought of instructive or cognitive content in a laconic form. The paper reveals that O. Shaigal introduces the term “political aphoristic”. Political aphoristic is considered to be language reflexes of political communication, a cultural trace, an active agent of political communication leaves in the language. The concept of “political aphorism” is characterized through the prism of political aphoristic. The article researches the appearance of the term “political aphorism” is associated with N. Bazhalkina. The paper points at the fact that understanding of the term “political aphorism” depends on the interpretation of political discourse. N. Bazhalkina observes that the aphorism reflects the political discourse in the unity of the two sides: the material (events and phenomena belong to the sphere of politics) and the abstract philosophical (reflection of the realities of human existence). The definition of the term “political aphorism” is proposed. The thorough analysis demonstrates that political aphorism criticizes, deeply comprehend social and political events, accumulate public consciousness in a didactic or ironic form, using different ways of expressive means and stylistic devices. According to our understanding, politically conscious versions of the population, such as writers, journalists, public figures etc. Can join the dialogue with the politics in the form of aphorisms. Its semantic content is found. The understanding of social and political life is built in the consciousness of the individual in the system of concepts: “power”, “state”, “nation”, “politics”, “democracy”, “people”, “law” etc. The internal content of aphorisms reflects the actual events of the current political situation. The subsystem of aphoristic is heterogeneous, functioning in a particular system. The following genres are distinguished: aphorism, proverb, maxim, title, slogan, motto, program statement, phrase-symbol, index-phrase. The paper also indicates such functions of political aphorism as modeling, regulatory, didactic, argumentative, regulatory, predictive and expressive etc.